Comparative Sensitivity of Intraoperative Motor Evoked Potential Monitoring in Predicting Postoperative Neurologic Deficits: Nondegenerative versus Degenerative Myelopathy. (August 2016) - Clark, Aaron J.; Safaee, Michael; Chou, Dean; Weinstein, Philip R.; Molinaro, Annette M.; Clark, John P.; Mummaneni, Praveen V.
Study Design: Retrospective review. Objective: Intraoperative motor evoked potential (MEP) monitoring in spine surgery may assist surgeons in taking corrective measures to prevent neurologic deficits. The efficacy of monitoring MEPs intraoperatively in patients with myelopathy from nondegenerative causes has not been quantified. We compared the sensitivity and specificity of intraoperative MEP monitoring in patients with myelopathy caused by nondegenerative processes to patients with degenerative cervicothoracic spondylotic myelopathy (CSM). Methods: We retrospectively reviewed our myelopathy surgical cases during a 1-year period to identify patients with degenerative CSM and CSM of nondegenerative causes and collected data on intraoperative MEP changes and postoperative new deficits. Categorical variables were analyzed by Fisher exact test. Receiver operator curves assessed intraoperative MEP monitoring performance in the two groups. Results: In all, 144 patients were identified: 102 had degenerative CSM and 42 had CSM of nondegenerative causes (24 extra-axial tumors, 12 infectious processes, 5 traumatic fractures, and 1 rheumatoid arthritis). For degenerative CSM, there were 11 intraoperative MEP alerts and 7 new deficits ( p < 0.001). The corresponding sensitivity was 71% and the specificity was 94%. In the nondegenerative group, there were 11 intraoperative MEP alerts and 3 deficits, which was not significant ( p > 0.99). The sensitivity (33%) and specificity (74%) were lower. Among patients with degenerative CSM, the model performed well for predicting postoperative deficits (area under the curve [AUC] 0.826), which appeared better than the nondegenerative group, although it did not reach statistical significance (AUC 0.538, p = 0.16). Conclusions: Based on this large retrospective analysis, intraoperative MEP monitoring in surgery for nondegenerative CSM cases appears to be less sensitive to cord injury and less predictive of postoperative deficits when compared with degenerative CSM cases.